The Australian and New Zealand dietetics graduate outcomes survey: A cross‐sectional study. Issue 4 (3rd May 2022) - Blair, Merran; Palermo, Claire; Gibson, Simone; Mitchell, Lana
Abstract: Aim: There is a paucity of comprehensive and current employment data for dietitians. It is unclear if, and where, dietetics graduates are being employed and if they are sufficiently prepared to meet workforce and community needs. The aim of this study was to identify employment outcomes for recent dietetics graduates from Australia and New Zealand at 4–6 months post degree completion. Methods: A cross‐sectional survey was distributed to graduates from accredited dietetics degrees across Australian and New Zealand. Those who completed their university study in 2020 were eligible to participate. Descriptive statistics and frequencies were analysed and open text answers underwent summative content analysis. Results: A total of 294 usable survey responses were received from 631 eligible graduates (response rate 47%). Seventy‐five percent of graduates were employed in any field and 60% were employed in a role that required their degree. The most common area of dietetics employment was private practice, followed by hospital practice. Most commonly, graduates who did not need their degree to get their job were employed in healthcare‐related roles, or nutrition‐ and food‐related roles. Conclusions: These findings are important for curricula development to ensure that students are suitably prepared for available employment opportunities. Work‐integrated learning experiences may need to shift focus to skill development, rather than a specific job role, to better prepare graduates for the jobs of the future. Further monitoring of employment outcomes is necessary to track changes over time.